2016
DOI: 10.1140/epjc/s10052-016-4527-5
|View full text |Cite
|
Sign up to set email alerts
|

Generalised model for anisotropic compact stars

Abstract: In the present investigation an exact generalised model for anisotropic compact stars of embedding class 1 is sought with a general relativistic background. The generic solutions are verified by exploring different physical aspects, viz. energy conditions, mass-radius relation, stability of the models, in connection to their validity. It is observed that the model presented here for compact stars is compatible with all these physical tests and thus physically acceptable as far as the compact star candidates R … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(95 citation statements)
references
References 41 publications
2
92
0
1
Order By: Relevance
“…We have shown that this is not the case and reduced them to the couple of inequalities in Eq. (26). Only Eq.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that this is not the case and reduced them to the couple of inequalities in Eq. (26). Only Eq.…”
Section: Discussionmentioning
confidence: 99%
“…This method has proved to be a fruitful mechanism to find new relativistic astrophysical models in recent investigations. Bhar et al [14][15][16], Maurya et al [17][18][19][20] and Newton Singh et al [21][22][23] have generated different families of physically acceptable Karmarkar spacetimes that describe the interior regions of acceptable stars. In these analyses a particular form of one of the potentials is made, which solves the Karmarkar condition, giving the second potential, eventually leading to an astrophysical model.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of ECs in modified theories has been carried out regarding a variety of cosmological issues like, f (R) gravity [75], f (R, L m ) gravity [76], f (R, T ) gravity [77], f (R, G) gravity [78], and f (G) gravity [79,80]. The stability of compact objects and their ECs have been analyzed in detail by various researchers [81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%